Analysis of potential categories of depression in older adults with chronic illness - Qu, Yiping; Sun, Xiaomin; Zhao, Ya (Frontiers in Psychology, 2026)
ObjectiveThis study aims to explore the prevalence of depression in older adults with chronic diseases and to identify heterogeneous subgroups within this population. Additionally, we seek to investigate the influencing factors associated with depressive conditions among older adults. This study aims to provide a foundational reference for the development of targeted intervention programs.MethodsThis study utilized data from the 2018 China Health and Aging Tracking Survey (CHARLS), including 5,878 older adults with chronic diseases. We explored potential categories of depression among these individuals through latent profile analysis. Additionally, one-way chi-square tests and one-way ANOVA were employed for single factor, while multi-factor correlation was identified via multinomial logistic regression analysis.ResultsA total of 5,878 older adults with chronic diseases were included in this study. The participants were categorized into four groups: low level (1,904; 32.4%), low level with high despair (304; 5.2%), medium level (2,963; 50.4%), and high level (707; 12.0%). Univariate analysis of variance revealed significant differences among all variables, except for the presence of only one child. In comparison to the low level group (i.e., control group), the factors influencing the high level group included anxiety, instrumental activities of daily living (IADL), living alone, self-assessment of current life and health, exercise, activity limitation, financial self-assessment, and marital status. For the medium level group significant factors included anxiety, living alone, health self-evaluation, alcohol use, exercise, and activity limitation. Influential factors for the low level with high despair group include health self-evaluation, exercise, engagement in regular physical labor, and economic self-assessment.LimitationsThe CES-D-10 scale may not fully capture the presence of depression in older adults with high levels of chronic illness.ConclusionDepression in older adults with chronic illnesses, stemming from both physical and psychological factors, can significantly impact their overall health status. Therefore, it is essential to provide more targeted healthcare services tailored to the diverse needs of this population in future community health initiatives. Such approaches aim to improve depressive symptoms and enhance the quality of life for older adults.